IMPLEMENTATION OF SCHOOL DIGITALIZATION TO IMPROVE LEARNING QUALITY - Lukman Wakum; Hamjah Bonso; Rani Maswati (Administratie: Jurnal Administrasi Publik, 2025)
This research is motivated by challenges in implementing school digitalization, such as suboptimal technological infrastructure and varying levels of human resource readiness (teachers and students), which have the potential to impact efforts to improve the quality of learning. This study aims to identify, understand, assess, and describe the researcher's findings regarding the implementation of school digitalization in improving the quality of learning. This research uses a descriptive qualitative approach, collecting data to provide an in-depth explanation of the phenomena occurring, using data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of school digitalization faces significant challenges in infrastructure and technology, particularly related to internet network stability and the availability of devices, which are key obstacles.